Konflik Peran Ganda Perempuan Pengusaha Industri Kecil di Kabupaten Bangkalan Madura - Nurita Andriani; - Faidal (Neo-Bis, 2008)
The critical problem that faced by women entrepreneur was the strain / conflict which appear between way of life and  career, the strain was reflected by conflict role. That’s were  business and household. That was the problem that faced by women entrepreneur of batik small business in Bangkalan Madura.　　　　This research was aimed to know the factors that influencde business-related factors, family-related factors, personal factor to the double role conflict of small business in Bangkalan. Batik small business  was used as a research object, because  over 50%  batik handycraf was women. This research placed  at Tanjung Bumi which use 54 respondens as the sample, which were taken from three villages, desa Tanjung, desa Telaga Biru, and  desa Paseseh.　　　　The result of this research showed that comfortability of life, self-respect, business satisfaction, time of work, children dan the liquidity of the business had significant influence to the double role conflict of the women entrepreneur in batik small business. Filling comfortable because she could help to increase the welfare of the family by having a business, were the domain factor which could eliminate the double role conflict to the women entrepreneur. Married happiness, worker and education had no significant influence to the double role conflict of the women entrepreneur.